Ir-Catalyzed α-Alkylation of Ketones with Alcohols: One-Step Access to Donepezil - Wang, Sen; Miao, Rui; Xia, Yanping; Wei, Yifei; Luo, Renshi; Ouyang, Lu (Synthesis, 2022)
We demonstrate an iridium-catalyzed alkylation of ketones with alcohols, which enables one-step access to donepezil, cyclic ketones, and linear ketones in high yields. A scale-up experiment shows the excellent practicability of this protocol. Comparative experiments show that a small amount of water is beneficial to the improvement of product yield.
Keywords: iridium-catalyzed; borrowing hydrogen; α-alkylation; Donepezil